Na superfície têxtil: narrativas em estampas de Ronaldo Fraga - Luciana Rothberg Vieira (2012)
This dissertation looks into the universe of meanings created by fashion designer Ronaldo Fraga in his production, which conceives narratives in the field of fashion, utilizing memory, affection and humor as means of expression. This research focuses on the analysis of the meaning of the imagery contained in his collections in the printed surfaces, considered as field of expression of his imagination, filled with symbols that reflect dynamically the contemporary moment.